Graphene oxide nano-domain formation via wet chemical oxidation of graphene - YANIK, SERHAT (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Chemical modification and functionalization of graphene is of great interest to alter its intrinsic properties. Among various methods, wet chemical oxidation is widely used for obtaining large quantities of graphene oxide or reduced graphene oxide. It is also often used as an intermediary step for further functionalization of the graphene. This work presents a microscopic study of the oxidation of single layer graphene on SiO2/Si substrate via wet chemistry. In addition to a uniform graphene oxide region growing at the edge, nano-sized graphene oxide domains within unoxidized graphene is observed. The graphene oxide nano-domain formation is attributed to the nonuniform impurity doping of the flakes which affect the local electrochemical reactivity of graphene. Graphene oxide nano-domain covered flakes which provide a long interface between the conducting graphene medium and the nano-domains, may be used as a template material for further functionalization to be used in novel electronic devices. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Graphene; Graphene oxide; Wet chemistry; Impurity doping; Reactivity; RAMAN-SPECTROSCOPY; LAYER GRAPHENE; DIAZONIUM FUNCTIONALIZATION; SINGLE-LAYER; LITHOGRAPHY; REACTIVITY; HYDROGENATION; SCATTERING; CHEMISTRY; SUBSTRATE